2001
DOI: 10.1093/jn/131.3.1106s
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Helicobacter pylori and Other Bacterial Infections by Garlic

Abstract: Louis Pasteur was the first to describe the antibacterial effect of onion and garlic juices. Historically, garlic has been used worldwide to fight bacterial infections. Allium vegetables, particularly garlic (Allium sativum L.) exhibit a broad antibiotic spectrum against both gram-positive and gram-negative bacteria. Noteworthy results published include the following: 1) raw juice of garlic was found to be effective against many common pathogenic bacteria-intestinal bacteria, which are responsible for diarrhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(109 citation statements)
references
References 14 publications
5
100
0
4
Order By: Relevance
“…For instance, garlic did not show much inhibitory activity in Liu and Nakano's study (41) despite extensive literature indicating otherwise (40,42). Liu and Nakano postulated that these differences may have been related to use of dried garlic powder in their study compared to other studies which relied on other forms of garlic (41).…”
Section: Health Effectsmentioning
confidence: 83%
“…For instance, garlic did not show much inhibitory activity in Liu and Nakano's study (41) despite extensive literature indicating otherwise (40,42). Liu and Nakano postulated that these differences may have been related to use of dried garlic powder in their study compared to other studies which relied on other forms of garlic (41).…”
Section: Health Effectsmentioning
confidence: 83%
“…Historically, garlic has been used worldwide to fight bacterial infections. It is well documented that garlic preparation exhibit a wide spectrum of antibacterial activity against gram-negative and grampositive bacteria such as Escherichia coli, Salmonella, Staphylococcus, Streptococcus, Bacillus and Clostridium (Ankri & Mirelman 1999;Sivam 2001). El-Astal (2004) also reported the high antibacterial efficacy of garlic extract on certain pathogenic grampositive bacteria (Staph.…”
Section: Excreta Microbiotamentioning
confidence: 99%
“…Investigations have shown that garlic plays an important pharmacological role as an antibacterial, antiviral, antifungal agent as well as a remedy for intestinal disorders, flatulence, worms, respiratory infections, skin diseases, wounds, symptoms of ageing and many other ailments (Amagase et al 2001). Moreover, garlic has several beneficial effects for either human or animals having antioxidant, antihypertensive properties (Sivam 2001) as well as prevents heart disease and cancer and diabetes (Konjufca et al 1997;Amagase et al 2001). It has also been reported that fresh dietary garlic can help to improve the immune stimulatory effect during Newcastle disease, avian influenza and bursal disease challenge in birds (Jafari et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to exhibit antimicrobial, antioxidant, and anti-hypertensive properties (Konjufca et al, 1997;Sivam, 2001). As a natural feed additive, garlic has been reported to improve broiler growth, feed conversion ratio and decreased mortality (Jagdish & Pandey, 1994;Tollba & Hassan, 2003).…”
Section: Introductionmentioning
confidence: 99%